Under Bump Metallurgy (UBM)-a technology review for flip chip packaging - Mohd Khairuddin Md Arshad; Uda Hashim; Muzamir Isa (Department of Mechanical Engineering, University Malaya, 2008)
Full text of this article is also available at http://mechanical.eng.um.edu.my/